Emerging threats of HPAI H5N1 clade 2.3.4.4b in swine: knowledge gaps and the imperative for a One Health approach - Mena-Vasquez, Juan; Marco-Fuertes, Ana; Culhane, Marie; Torremorell, Montserrat (Frontiers in Veterinary Science, 2025)
Highly pathogenic avian influenza (HPAI) H5N1 represents a significant threat to wildlife, livestock, and public health. The recent detection of HPAI H5N1 clade 2.3.4.4b genotypes B3.13 and D1.1 in dairy cows, poultry, wild birds, wild mammals, and humans, along with the recent detection of D1.2 genotype in outdoor pigs, reflects an accelerated shift in the ecological and transmission dynamics of the virus. Given the pigs’ role in influenza ecology, these shifts present a serious threat to the swine industry and public health, accentuating the urgency for a coordinated One Health response. However, the current understanding of swine influenza, particularly in preventing and preparing for potential HPAI H5N1 incursions, has not been fully discussed. Furthermore, the consequences of such incursions on the swine industry and consequently on public health have not been explored extensively. This review addresses the knowledge gaps related to HPAI H5N1 clade 2.3.4.4b infections in pigs. Assessing the risks of HPAI H5N1 in pigs and the consequences for cross-species transmission is crucial. Preventing the introduction of HPAI into pigs and minimizing spillover risks through evidence-based strategies is vital to ensuring food security, maintaining a safe food supply, sustaining animal production systems, and preventing human infections, including potential pandemics.